Pengembangan Media Pembelajaran Papan Kata pada Mata Pelajaran Bahasa Indonesia Kelas II SDN 28 Mataram - Najwa Alifia Rahman; Sukri; Aisa Nikmah Rahmatih (Mataram University, 2026)
Language proficiency is a fundamental and essential skill for elementary school students, particularly in the lower grades. This study aimed to develop a word board learning media for Grade II Indonesian language subjects at SDN 28 Mataram. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were all Grade II students of SDN 28 Mataram, with the research object being the word board learning media in Indonesian language instruction. Data collection techniques included tests, interviews, and questionnaires. The media validation results obtained a score of 96.25% in the very valid category and could be used without revision. The material expert validation result achieved a score of 80% in the valid category and could be used with revision. The language expert validation result obtained a score of 68.75% in the valid category. The practicality test result of the word board media achieved a percentage score of 98% in the very practical category. The effectiveness test result obtained a significance value of 0.56 in the effective category. These findings indicate that the word board learning media in the Indonesian language subject for Grade II at SDN 28 Mataram is proven to be effective in improving students’ understanding of hazardous objects material in the Grade II Indonesian language subject.